Improving Shear Strength Parameters of Sandy Soil using Enzyme-Mediated Calcite Precipitation Technique - Heriansyah Putra; Hideaki Yasuhara; Naoki Kinoshita; Erizal .; Tri Sudibyo (Institute of Research and Community Outreach - Petra Christian University, 2018)
Several methods have been established for their various potential applications as soil improvement technique, and recently the application of grouting technique using biological process have been proposed. This study discussed the applicability of enzyme-mediated calcite precipitation (EMCP) in improving the shear strength parameters of sandy soil. In this study, soil specimens were prepared and treated with the grouting solutions composed of urea, calcium chloride, magnesium sulfate and enzyme of urease. Evolutions in the cohesion and internal friction angle of the improved soil were examined through the direct shear tests. The presence of the precipitated materials, comprising 4.1 percent of the soil mass of the treated sand, generated a cohesion of 53 kPa. However, contrary to the improvement of cohesion, the friction angle is relatively constant. It indicated that the application of the EMCP technique has no significant impact on the friction angle